A PROSPEK PENGELOLAAN KEUANGAN BANK SYARIAH DI INDONESIA - zumaroh zumaroh (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2018)
At present, Islamic banking in Indonesia is growing up fastly and very fantastic with the unique financial management system. The global monetary crisis have brought it’s cleverness in the Islamic banking development besouse the world societies, the experts, and the prudence makers desire to apply shariah concept seriously. The Islamic financial institutions (including Islamic banking) appear as one of Shariah concept applications with no refusal. Even it’s excepted because of the real influence, so that Islamic banking is prospecting in the future. Its offers the real investment and benefit (revenue) by profit – lost sharing system. The interest-free concept in Islamic banking operation makes it different from conventional banking that based on interest-fee. Besides, the application of Good Corporate Governance in Islamic banking is expected to be able to increase the precious for stakeholders. The GCG aplication is excpected to increase publics trust to Islamic banking financial management system, maintain the growth of Islamic financial industries and the stability of whole financial system, and bring the Islamic finance institutions into of playing field level that equal with other international finance institutions.